Rediscovering the Final Palaeolithic-Mesolithic Settlement at Pabartoniai, a Site on the River Neris - Gudaitienė, Gabrielė (Archaeologia Lituana, 2017)
In this article, the primary results of the latest archaeological investigation in Pabartoniai site are represented. The site, in which the earliest finds could be dated to Final Palaeolithic and Mesolithic, was rediscovered in 2014 and has been excavated for two seasons. Prehistoric structures, flint find assemblage and some archaeobotanical remains provide an opportunity to discuss some questions considering the occupation of the site. However, at the same time, some problems regarding the reconstruction of the first settlement of the river Neris lower reaches are raised, as the archaeological finds are mixed with the material of the later settlement.